Literary Meaning of Anxiety reflected by the Servant found in ‘Appointment in Samarra’ by Somerset Maugham - Siti Fatimah; Septi Koestiani (STKIP PGRI SIDOARJO, 2020)
This research was conducted to describe the semantics analysis of the literary meaning of anxiety in the story ‘Appointment in Samara’ written by Somerset Maugham. This research applied descriptive qualitative method. The instrument was the researcher himself, and supporting by the secondary instrument called the scripted text of the story examined. The data collection were taken from internet, it was the text of the story ‘Appointment in Samara’. To analyze all data, this study used the theory of literary meaning proposed by Lyons (1977). The data were indentified, then were classified, were displayed, and were described. The results of the study showed there were three kinds defense mechanism of reactions in anxiety namely: (1) regression, (2) repression, and (3) rationalization.